2009
DOI: 10.1128/jcm.00360-09
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly High Proportion of Ancestral Manu Genotype Mycobacterium tuberculosis Strains Cultured from Tuberculosis Patients in Egypt

Abstract: Tuberculosis is one of the important public health problems in Egypt. However, limited information on the Mycobacterium tuberculosis genotypes circulating in Egypt is available. A total of 151 M. tuberculosis strains were characterized by spoligotyping. The results revealed that 74.8% of M. tuberculosis isolates grouped into 13 different clusters, while 25.2% had unique spoligotype patterns. Comparison with an international spoligotyping database (the SITVIT2 database) showed that types SIT53 (T1 variant) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 22 publications
4
27
2
Order By: Relevance
“…Soon afterwards, it was tentatively subdivided into the Manu1 (deletion of spacer 34), Manu2 (deletion of spacers 33 and 34), and Manu3 (deletion of spacers 34 to 36) sublineages, and it was suggested that it could represent an ancestral clone of principal genetic group (PGG) 1 strains (4). Manu lineage strains were reported from Saudi Arabia (2) and Tunisia (17) and more recently in a study from Egypt, where it represented as much as 27% of all isolates (15). However, according to a recent report, a fraction of Manu2 patterns could also arise due to mixed infection by a strain belonging to evolutionarily recent H, LAM, X, and T lineages with a Beijing strain, a risk that may be excluded by looking for genomic deletion of region of difference RD105, which is characteristic of the Beijing lineage (26).…”
Section: Resultsmentioning
confidence: 99%
“…Soon afterwards, it was tentatively subdivided into the Manu1 (deletion of spacer 34), Manu2 (deletion of spacers 33 and 34), and Manu3 (deletion of spacers 34 to 36) sublineages, and it was suggested that it could represent an ancestral clone of principal genetic group (PGG) 1 strains (4). Manu lineage strains were reported from Saudi Arabia (2) and Tunisia (17) and more recently in a study from Egypt, where it represented as much as 27% of all isolates (15). However, according to a recent report, a fraction of Manu2 patterns could also arise due to mixed infection by a strain belonging to evolutionarily recent H, LAM, X, and T lineages with a Beijing strain, a risk that may be excluded by looking for genomic deletion of region of difference RD105, which is characteristic of the Beijing lineage (26).…”
Section: Resultsmentioning
confidence: 99%
“…Using this approach, one considers that all intermediate stages are present within the sample analysed by including first the individual that shows the greatest number of possible linkages to other individuals in the population studied. We used this method to highlight the phylogenetic links between two spoligotypes differing by changes observed in direct variable repeats (Helal et al 2009). Consequently, the lengths of the branches in the tree indicate the level of change induced by the loss or gain of spoligotype spacers in the 43-oligonucleotide format that induce a shift from one allele to another; the solid lines represent a single spacer change, dotted lines represent two spacer changes (black) or more than two spacer changes (gray).…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Phylogenetic analysis -The evolutionary relationships among all of the observed spoligotypes were studied by drawing a minimum spanning tree (MST) with BioNumerics software as reported previously (Helal et al 2009). MST is an undirected network in which all of the samples are linked together with the fewest possible linkages between nearest neighbours.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…24 Although Egypt is not on the WHO list of 22 high-TB-burden countries, it is considered one of the high-burden countries in WHO's Eastern Mediterranean region. 23 Tubercular decay has been found in the spines of Egyptian mummies from 3000-2400 BC. 25 The fi rst evidence that human tuberculosis was present in ancient Egypt came from typical macroscopic osseous changes in human remains, which were in this instance the well preserved Egyptian mummies.…”
Section: Tb Problem In Mansouramentioning
confidence: 99%
“…Tuberculosis is one of the important public health problems 23 . It constitutes a major public health problem after HCV and bilharziasis.…”
Section: Tb Problem In Mansouramentioning
confidence: 99%